Education policy, globalization, commercialization: An interview with Bob Lingard by David Hursh. (May 2017) - Hursh, David
In this interview with David Hursh, Bob Lingard comments on his current and/or recently completed research projects in respect to new modes of global governance in schooling and the complementarity between international large scale assessments and national testing. He also looks at a project that, in conjunction with school leaders, teachers, students, and community, developed an alternative mode of educational accountability to the currently dominant, simple, top-down, test-based mode. Here schools and their communities would be enabled to give an account of their multiple achievements of various kinds and draw on qualitative, as well as quantitative data. Another project has focused on the ways in which datafication in education opens up spaces for profit-motivated edu-businesses. Here data infrastructures are seen to actually structure schooling systems in particular ways and also work in networked governance across edtech companies and state actors. The final project considered is funded by a teacher union and documents the extent and nature of commercialisation of public schooling in Australia, what enables this, and teachers' and school leaders' attitudes to commercialisation.